Pelatihan Pembuatan Media Pembelajaran untuk Guru SMA Dr. Soetomo Surabaya Menggunakan CANVA - Ayouvi Poerna Wardhanie; Endra Rahmawati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
SMA Dr. Soetomo Surabaya is one of the private high schools in Surabaya that has a vision to create a school with a religious, nationalistic, independent, high-achieving and global perspective. SMA Dr. Soetomo Surabaya has around 50 teachers and education personnel and 654 active students in the odd semester of 2024/2025. To improve the quality of teachers and the learning process at school, SMA Dr. Soetomo sent 33 teachers to learn about creating learning media using the Canva application. This application is a platform for creativity in managing learning content in various forms, such as power points. There are many templates from power points that have been provided in the Canva application that can be selected by teachers to support the creation of learning media. Teachers can innovate in arranging power point components, inserting supporting components such as images/audio/video/ animation to attract students' attention. The results of participant feedback at the end of the training showed that 97,8% Teachers can understand the material given and trainers can provide innovative learning media solutions according to the current needs of students.